Archiv X : Ermittlungen der Gegenwartskunst. - Sturm, Martin; Groys, Boris; Zendron, Rainer; Bruckschwaiger, Karl; Idensen, Heiko; Bianchi, Paolo; Zarzer, Brigitte; von Bismarck, Beatrice; S.-Sturm, Eva; Madlener, Elisabeth; Krasny, Elke; O.K Centrum für Gegenwartskunst des Landes Oberösterreich, Linz (Linz : O.K Centrum für Gegenwartskunst des Landes Oberösterreich, 1998)
Clegg & Guttmann ; Anderson Barbata, Laura ; Bublex, Alain ; Bijl, Guillaume ; Klopf, Karl-Heinz ; Brombacher, Jörg ; Heid, Klaus ; Collins, Nicolas ; Corillon, Patrick ; Rennó, Rosangela ; Kósa, Eva-Maria ; Struber, Katharina ; Marclay, Christian ; Beusch ; Cassani ; fuchs-eckermann
O.K. Centrum für Gegenwartskunst Oberösterreich, Linz, 24. April bis 17. Juli 1998
kunstcatalogus